2020
DOI: 10.3389/fped.2020.00155
|View full text |Cite
|
Sign up to set email alerts
|

Serious Hemorrhagic Complications After Successful Treatment of Hematopoietic Stem Cell Transplantation-Associated Thrombotic Microangiopathy With Defibrotide in Pediatric Patient With Myelodysplastic Syndrome

Abstract: Background: Transplant-associated thrombotic microangiopathy (TAM) is a life-threatening complication of hematopoietic stem cell transplantation (HSCT). There is some evidence of endothelial injury playing a significant role in TAM development. The efficacy of defibrotide was demonstrated for prophylaxis and treatment of another HSCT-associated endothelial damage syndrome-liver veno-occlusive disease. The data for defibrotide usage in TAM are limited. Case Description: A 9-year old boy underwent HSCT from a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Another supportive treatment for HSCT-TMA, defibrotide is approved for the treatment of hepatic veno-occlusive disease, also known as sinusoidal obstruction syndrome, a complication following HSCT [63]. Retrospective analyses and case series of defibrotide therapy have reported responses in patients with HSCT-TMA [46,[64][65][66][67] and a prospective pilot study suggested prophylactic defibrotide use reduces the incidence of HSCT-TMA [68], but increased bleeding and hemorrhagic complications were reported with defibrotide use in these studies [65][66][67][68]. Historically, another approach to treat HSCT-TMA has been to withhold or modify calcineurin inhibitors [22], but recent data have shown that continuing immunosuppressants does not impact resolution of HSCT-TMA or survival in patients with HSCT-TMA.…”
Section: Supportive Therapymentioning
confidence: 99%
“…Another supportive treatment for HSCT-TMA, defibrotide is approved for the treatment of hepatic veno-occlusive disease, also known as sinusoidal obstruction syndrome, a complication following HSCT [63]. Retrospective analyses and case series of defibrotide therapy have reported responses in patients with HSCT-TMA [46,[64][65][66][67] and a prospective pilot study suggested prophylactic defibrotide use reduces the incidence of HSCT-TMA [68], but increased bleeding and hemorrhagic complications were reported with defibrotide use in these studies [65][66][67][68]. Historically, another approach to treat HSCT-TMA has been to withhold or modify calcineurin inhibitors [22], but recent data have shown that continuing immunosuppressants does not impact resolution of HSCT-TMA or survival in patients with HSCT-TMA.…”
Section: Supportive Therapymentioning
confidence: 99%